Molecular Mechanisms in Mood Regulation Involving the Circadian Clock - Albrecht, Urs (Frontiers in Neurology, 2017)
The circadian system coordinates activities and functions in cells and tissues in order to optimize body functions in anticipation to daily changes in the environment. Disruption of the circadian system, due to irregular lifestyle such as rotating shift work, frequent travel across time-zones, or chronic stress, is correlated with several diseases such as obesity, cancer and neurological disorders. Molecular mechanisms linking the circadian clock with neurological functions were uncovered suggesting that disruption of the clock may be critically involved in the development of mood disorders. In this mini-review I will summarize molecular mechanisms in which clock components play a central role for mood regulation. These mechanisms are part of the monoaminergic system, the HPA-axis and neurogenesis.